Kepuasan Pasien Terhadap Pelayanan Puskesmas Ngemplak Simongan Kecamatan Semarang Barat Kota Semarang - Wahyu Eko Giri Kusumo; Dewi Sri Rahayu; Rani Tiara Desty (Universitas Ivet, 2023)
Patient satisfaction is an assessment of the good or bad quality of health services received by patients. The background of this research is that the Ngemplak Simongan Public Health Center, Semarang City, in carrying out health duties has not yet achieved the desired goals, in general there are still weaknesses. The aim of the research was to determine the level of service quality at the Ngemplak Simongan Health Center. Quantitative research using a descriptive observational study design, using a cross-sectional research design approach. This research was conducted at the Ngemplak Simongan Health Center in December 2022. Sampling used the Purposive Sampling Method. This research instrument used a questionnaire, how to collect data by interview and Google form. The results of the research are good product quality, poor price, poor service quality, good reliability, good tangibility, poor assurance, good emotional factor, good convenience. Suggestions for this research institution can be used as material for consideration in efforts to improve the quality of health services.